Семантическое развитие концепта СКАНДАЛ и его деривационные маркеры в русских и польских медиатекстах - Koriakowcewa, Elena (Acta Neophilologica, 2020)
This article is devoted to the tendencies in the semantics of words скандалand skandal and the derivation with the help of the -gate suffixoid in the modern Russian and Polish mass media discourse being the main environment for the emergence and spreading of scandals. The modern scandal becomes an attention attracting strategy. As a result, new semantic features and a positive connotation appear in the semantics of the words скандал and skandal. The -gate suffixoid is used to derive the terms that may suggest unethical behaviour and a cover-up of scandal, particularly in politics and government.